Strengthening Social, Moral, and Religious Character Values in Congregational Prayer Activities at Muhammadiyah Elementary School, Bantul City - -, Maya Kartika Sari; Budiyono (IAIN Ambon, 2025)
This study aims to analyze the social, moral and religious character values ​​in the implementation of congregational prayers at SD Muhammadiyah Bantul Kota. The type of research is descriptive qualitative research. This research was conducted in January - February 2025. The subjects of the study were 6 teachers, 20 students, and 5 guardians. Data collection techniques in this study were observation, semi-structured interviews, and documentation. Data analysis techniques in the study refer to Miles Huberman's theory, namely data reduction, data display and data conclusion. The results of the study show that congregational prayers at SD Muhammadiyah Bantul Kota have been implemented well and run optimally. The implementation of congregational prayers at SD Muhammadiyah Bantul Kota can strengthen social, moral and character values ​​in students, namely the values ​​of social concern and social solidarity between students; foster values ​​of tolerance and cooperation between students; values ​​of discipline, fostering deep obedience and compliance when performing congregational prayers; Cultivating religious values, namely as a center for social preaching and increasing faith and devotion to God Almighty and instilling the values ​​of akhlakul kharimah in students. The implementation of congregational prayers at Muhammadiyah Elementary School Bantul City must be maintained and implemented optimally in order to continue to improve the quality of students who are intelligent, religious, and have noble character